1999
DOI: 10.1287/mnsc.45.12.1631
|View full text |Cite
|
Sign up to set email alerts
|

Price Versus Production Postponement: Capacity and Competition

Abstract: T his article presents a comparative analysis of possible postponement strategies in a two-stage decision model where firms make three decisions: capacity investment, production (inventory) quantity, and price. Typically, investments are made while the demand curve is uncertain. The strategies differ in the timing of the operational decisions relative to the realization of uncertainty.We show how competition, uncertainty, and the timing of operational decisions influence the strategic investment decision of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
133
2
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(137 citation statements)
references
References 24 publications
1
133
2
1
Order By: Relevance
“…Banker et al [2] investigated the effect of competitive intensity on the equilibrium levels of quality and their study found that the relationship between quality and competitive intensity depends on the increased competition and other parameters. Van Mieghem and Dada [43], in their study of the value of various forms of postponement, developed a single period model for retailers offering a homogeneous good.…”
Section: ⅱ Literature Reviewmentioning
confidence: 99%
“…Banker et al [2] investigated the effect of competitive intensity on the equilibrium levels of quality and their study found that the relationship between quality and competitive intensity depends on the increased competition and other parameters. Van Mieghem and Dada [43], in their study of the value of various forms of postponement, developed a single period model for retailers offering a homogeneous good.…”
Section: ⅱ Literature Reviewmentioning
confidence: 99%
“…Anupindi and Jiang (2008) develop the optimal capacity, production and pricing decisions in a duopoly setting. Van Mieghem and Dada (1999) shed light on the relative value of production postponement and price postponement under demand uncertainty. Anderson et al (2006) highlight the efficacy of backorders relative to other instruments in mitigating the impact of stockouts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The retailer will receive her orders or a portion of her orders, depending upon the actual capacity allocation of the suppliers, before the selling period. Note that there is no price and production postponement in our model, i.e., the retailer must decide unit sales prices and order quantities before actual supply or demand is realized (Van Mieghem and Dada, 1999). In this study, we let q i ¼ z i  d i , where z i is the stock factor of product i (Petruzzi and Dada, 1999;Wang et al, 2004;Weng, 1997).…”
Section: The Basic Modelmentioning
confidence: 99%